Application of Variational Mode Decomposition in Wind Power Fault Diagnosis - Wu Yingjie; Zhen Chenggang; Liu Changliang (Jixie chuandong)
As to mode mixing problem of empirical mode decomposition（ EMD） and local mean decomposition（ LMD） when they are applied to field data decomposition,a new wind turbine fault diagnosis method based on variational mode decomposition（ VMD） is put forward,and then it is applied to the wind power drivetrain system for imbalance fault diagnosis. The result shows that VMD can effectively avoid the mode mixing phenomenon caused by noise and impulse. It has a good effect on the diagnosis of unbalanced fault.